2019
DOI: 10.1088/1742-6596/1282/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mild steel from corrosion using methanol extract of avocado (Persea americana mill) seeds in a solution of sulfuric acid

Abstract: Avocado seeds have been studied for use as corrosion inhibitors of mild steel in a solution of 0.75 M sulfuric acid. Corrosion inhibition efficiency at a concentration of 10 g / L avocado seed extract (ASE) was obtained at 74.56% with weight loss method and 68.38% with potentiometric polarization method. Corrosion inhibition efficiency was found to be greater with increasing ASE concentration. Polarization studies show that the avocado seed extract is a mixed corrosion inhibitor. SEM images on mild steel with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…From the FTIR, ASPE had chemical functional groups that served as a green corrosion inhibitor. With similar results, Gusti et al, 2019 [21], concluded that the obtained compound from avocado seed was rich in polysaccharides, due to its functional groups, with a small quantity of tannin, among other compounds. Consequently, the derived inhibitor from avocado seed possibly contained nitrogen and oxygen atoms (Figure 8) in the aromatic ring and the functional group, which are generally found in other corrosion inhibitor structures with high inhibitory properties [25].…”
Section: Ftir Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…From the FTIR, ASPE had chemical functional groups that served as a green corrosion inhibitor. With similar results, Gusti et al, 2019 [21], concluded that the obtained compound from avocado seed was rich in polysaccharides, due to its functional groups, with a small quantity of tannin, among other compounds. Consequently, the derived inhibitor from avocado seed possibly contained nitrogen and oxygen atoms (Figure 8) in the aromatic ring and the functional group, which are generally found in other corrosion inhibitor structures with high inhibitory properties [25].…”
Section: Ftir Analysismentioning
confidence: 67%
“…Avocado seed contains aromatic rings and heteroatoms, indicating that it can be used as a high-performance and sustainable corrosion inhibitor. Other researchers have also reported the influence of avocado oil and seed for other materials [20][21][22][23][24][25]. Thus, this study was designed to study the potential of avocado seed extracts as a green corrosion inhibitor that is environmentally friendly, nontoxic, and cheap for API 5L X65 steel usually used for pipelines in 1 M H 2 SO 4 solution.…”
Section: Introductionmentioning
confidence: 99%
“…Avocado seeds are recognised to contain various bioactive and functional substances, which are important features as corrosion inhibitors. However, inadequate management of this waste, which is generated in significant amounts and sometimes disposed of by burning or indiscriminate disposal, can lead to environmental nuisances and pollution [33,34]. Therefore, researchers have started to use avocado seeds as corrosion inhibitors because they form a protective oxide film on various components (especially steel) against corrosion [33][34][35].…”
Section: The Development Of Nanoparticle Inhibitor From Avocado Seed ...mentioning
confidence: 99%
“…To increase the activity of the AS-SAM films formed over the copper electrode for methanol electrooxidation reaction, Ni particles, which have good methanol activity, [45,49,50] were precipitated over the Cu/AS-SAM surface. For this aim, the Cu/AS-SAM electrode was dipped into a Ni deposition bath (1% NiCl 2 .6H 2 O).…”
Section: As/sam(ni) Modified Copper Electrodesmentioning
confidence: 99%
“…AS contain functional molecules that have not been properly evaluated but such as tannin, flavonoid saponin, quinone, tannin, terpenoid, and starch. [45,46] In this context, corrosion researchers are making efforts to develop these non-toxic and economically obtained environmentally friendly compounds as corrosion inhibitors, which are contained in a waste that cannot be reasonably evaluated, such as the AS. The components in the avocado seed are indicated in detail by Indatri et al [47] Therefore, avocado fruits and their wastes have been used in different applications.…”
Section: Introductionmentioning
confidence: 99%